České dějepisectví v letech 1938-1945. Část II. - Pánek, Tomáš, 1986-; Borovský, Tomáš, 1972-; Masarykova univerzita. Historický ústav (2020)
Disertační práce analyzuje české dějepisectví v letech 1938-1945, a to ve srovnávací a vztahové perspektivě s historiografií sudetoněmeckou a slovenskou. Analyzovány jsou čtyři dimenze české historické vědy, a to 1. institucionální (instituce provozu historické vědy), 2. mediální (knižní nakladatelství a rozhlas, s nimiž čeští dějepisci spolupracovali), 3. profesionální (samotní historikové) a 4. dimenze adresátů (lidí, jimž byla historiografická produkce určena). Tyto dimenze jsou propojeny na bázi komunikace, když z dimenze institucionální a profesionální proudí pomocí dimenze mediální konkrétní obrazy dějin (historické narativy) ke svým adresátům. Tyto narativy jsou v práci také analyzovány. Disertační práce pracuje s šesti základními tezemi: 1. česká historiografie přejala po Mnichovské dohodě národně-obrannou úlohu; 2. došlo k její silné nacionalizaci (v českém smyslu); 3. zaujala silně protiněmecká stanoviska a interpretace dějin; 4. došlo k obratu od prozápadního ukotvení českýc
Ph.D. thesis analyzes Czech historiography in the years 1938-1945 in comparison and relation perspective with Sudeten German and Slovak historiography. Four dimensions of Czech historical science are analyzed: 1. institutional (institutions of historical science), 2. medial (publishing houses and radio with which Czech historians cooperated), 3. professional (historians themselves) and 4. dimensions of recipients (people to whom historiographic production was intended). These dimensions are interconnected on the basis of communication when concrete images of history (historical narratives) flow from their institutional and professional dimensions to their recipients through the medial dimension. These narratives are also analyzed. Ph.D. thesis works with six basic theses: 1. Czech historiography assumed a national defense role after Munich; 2. it was strongly nationalized (in the Czech sense); 3. took strong anti-German views and interpretations of history; 4. there has been a diversio
Vedoucí práce: Tomáš Borovský
Dizertace (Ph.D.)--Masarykova univerzita, Filozofická fakulta, 2020
Keywords: 1938-1945; 20. století; historiografie -- Česko -- 20. století; historici -- Česko -- 20. století; interpretace dějin -- Česko -- 20. století; historický výzkum -- Česko -- 20. století; historiography -- Czechia -- 20th century; historians -- Czechia -- 20th century; interpretation of history -- Czechia -- 20th century; historical research -- Czechia -- 20th century; disertace; disertations